Republic of Serbia : Report on Observance of Standards and Codes; Fiscal Transparency Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This report provides an assessment of fiscal transparency practices in Serbia in relation to the requirements of the IMF Code of Good Practices on Fiscal Transparency. Serbia has made solid advances in fiscal transparency in recent years, but there are still some major shortcomings. This report recommends that effective prioritization and execution of the budget process should be strengthened by integrating the National Investment Plan consistently into budget preparation and reporting. Commitment control should also be fully enforced so that any expenditure arrears can be comprehensively monitored.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet